Dune messiah - Herbert, Frank 1920-1986 (Berkley Pub. Co., 1970)
They made him a god through generations of controlled breeding and a lifetime of training, giving him more than human powers. But Paul Atreides would not be their tool, and the sisterhood of the Bene Gesserit set out to overthrow him